A Convenient Diels-Alder Approach toward Potential Polyketide-like Antibiotics Using α-Activated α,β-Unsaturated 4,4-Dimethyl-1-tetralones as Dienophiles - Chia-Jui Lee; Manickavasakam Ramasamy; Hsuan-Hao Kuan; Chien-Huang Wu; Chein-Chung Lee; Jinq-Chyi Lee; Kak-Shan Shia (Molecules, 2023)
Making use of a Diels–Alder approach based on various α,β-unsaturated 2-carbomethoxy-4,4-dimethyl-1-tetralones as novel dienophiles, the corresponding polycyclic adducts could be efficiently synthesized in good to high yields (74~99%) in the presence of Lewis acid (e.g., SnCl4). Accordingly, a synthetically useful platform is established to provide a focused aromatic polyketide-like library for screening of potential natural and non-natural antimicrobial agents.